Chemopreventive effect of Punica granatum in human lung carcinoma A549 cells - Nik Abdul Malek, Nik Nurasyikin; Abdul Ghani, Radiah (2014)
INTRODUCTION: Lung cancer is the most common type of cancer which the mortality rate increases year by year. Therapeutic drug could not control the progression of cancer effectively and it is also contributing to the side effects. Hence, alternative strategy such as chemoprevention using natural product should be investigated. P. granatumor pomegranate is one of the prophetic foods which has a potential to be a chemopreventive agent. It is rich in phytochemicals and has been used as medicine. This study is aimed to evaluate the anti-proliferative effect of the pomegranate on the growth of human lung carcinoma A594 cells. MATERIALS AND METHODS: The cytotoxicity test had been conducted by using MTT assay. The effect of pomegranate juice on A549 cancer cells growth and protein content were evaluated by trypan blue exclusion assay and Lowry assay, respectively. RESULTS AND DISCUSSION: The result showed that various concentrations of pomegranate juice treatment range from 0.0 to 3.0%resulted in a dose dependent inhibition of A549 cell growth. The inhibitory concentration, IC50 value was 0.8% after 48hr exposure, and 1.5% after 72hr and 96hr exposure. At the concentration of 1%, inhibition of growth was observed by decreased in cell number and protein content. From the results, the decreased of the protein content was lowered as compared to the untreated A549 cells. CONCLUSION: This preliminary study shown that, the pomegranate juice could inhibit the proliferation of A549 cancer cells. Hence, it could be a good strategy to prevent or slow the growth of cells.